2020
DOI: 10.3390/ijgi9030173
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Crop Water Deficit in Lower Bari Doab, Pakistan Using Reflection-Based Crop Coefficient

Abstract: There is a global realization in all governmental setups of the need to provoke the efficient appraisal of crop water budgeting in order to manage water resources efficiently. This study aims to use the satellite remote sensing techniques to determine the water deficit in the crop rich Lower Bari Doab Canal (LBDC) command area. Crop classification was performed using multi-temporal NDVI profiles of Landsat-8 imagery by distinguishing the crop cycles based on reflectance curves. The reflectance-based crop coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Their results showed that almost all of the water quality parameters have correlations with Rapid Eye reflection higher than 0.80. In Javed et al [27], a remote sensing technique was used to estimate crop water deficit. Crop classification was determined by NDVI using crop cycles based on reflectance curves.…”
Section: Content Of the Special Issuementioning
confidence: 99%
“…Their results showed that almost all of the water quality parameters have correlations with Rapid Eye reflection higher than 0.80. In Javed et al [27], a remote sensing technique was used to estimate crop water deficit. Crop classification was determined by NDVI using crop cycles based on reflectance curves.…”
Section: Content Of the Special Issuementioning
confidence: 99%